Associations of Serum Liver Function Markers With Brain Structure, Function, and Perfusion in Healthy Young Adults - Chen, Jingyao; Liu, Siyu; Wang, Chunli; Zhang, Cun; Cai, Huanhuan; Zhang, Min; Si, Li; Zhang, Shujun; Xu, Yuanhong; Zhu, Jiajia; Yu, Yongqiang (Frontiers in Neurology, 2021)
Background: Previous neuroimaging studies have demonstrated brain abnormalities in patients with hepatic diseases. However, the identified liver-brain associations are largely limited to disease-affected populations, and the nature and extent of such relations in healthy subjects remain unclear. We hypothesized that serum liver function markers within a normal level would affect brain properties. Method: 157 healthy young adults underwent structural, resting-state functional and arterial spin labeling MRI scans. Gray matter volume (GMV), regional homogeneity (ReHo) and cerebral blood flow (CBF) analyses were performed to assess brain structure, function and perfusion, respectively. Peripheral venous blood samples were collected to measure serum liver function markers. Correlation analyses were conducted to test potential associations between liver function markers and brain imaging parameters. Results: First, serum proteins showed relations to brain structure characterized by higher albumin associated with increased GMV in the parahippocampal gyrus and amygdala, and lower globulin and higher albumin/globulin ratio with increased GMV in the olfactory cortex and parahippocampal gyrus. Second, serum bilirubin was linked to brain function characterized by higher bilirubin associated with increased ReHo in the precuneus, middle cingulate gyrus, inferior parietal lobule and supramarginal gyrus, and decreased ReHo in the caudate nucleus. Third, serum alanine transaminase (ALT) was related to brain perfusion characterized by higher ALT associated with increased CBF in the superior frontal gyrus and decreased CBF in the middle occipital gyrus, angular gyrus, precuneus and middle temporal gyrus. More importantly, we found that CBF in the superior frontal gyrus was a significant mediator of the association between serum ALT level and working memory performance. Conclusion: These findings may not only expand existing knowledge about the relationship between the liver and the brain, but also have clinical implications for studying brain impairments secondary to liver diseases as well as providing potential neural targets for their diagnosis and treatment.